Litter size for gilts fed higher levels of folic acid and Riboflavin during gestation - Zhang, C.; Li, D.; Nelssen, Jim L.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We fed gilts diets containing either additional folic acid throughout gestation (1.5 g/ton, 4.5 lb/gilt daily), additional riboflavin (100 mg/gilt daily) from d 4 to 10 of gestation, both folic acid and riboflavin, or neither supplement All diets provided all KSU recommended allowances for all other nutrients. Neither farrowing rate nor litter size was affected by the treatments.
Keywords: Swine; VitB; Riboflavin; Gestation; Litter; Sow; Performance